ANALYSIS OF THE LEGAL BACKGROUND REGARDING THE ACCESS TO SPACE IN ROMANIAN AQUACULTURE - Erzsebet OLARIU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In Romania the largest spaces used for aquaculture are under the management of the National Administration ''Romanian Waters”, of the National Agency for Fisheries and Aquaculture and of some territorial administrative units. Each have separate regulations regarding the transmission of space use. Each has separate regulations on the use of space use. This paper has looked for an answer to the question: would it be beneficial if there was a single regulation for the cost and other conditions of use of aquaculture space? For this purpose, were studied data from national institutions and community institutions, there were talk with specialists in the fisheries sector, and has been studied the position of one Romanian fish farmers association. The study concludes that the road to a common interest, both economic and social, is bearing fruit and is above a self-interest, and does not violate the right to property or the good manifestation of property.